Laying the foundation for an International Classification of Functioning, Disability and Health Core Set for community-dwelling elderly adults in primary care: the clinical perspective identified in a cross-sectional study. Issue 11 (23rd November 2020) - Book, Stephanie; Ulbrecht, Gudrun; Tomandl, Johanna; Kuehlein, Thomas; Gotthardt, Susann; Freiberger, Ellen; Graessel, Elmar
Abstract : Objectives: Having more information about the biopsychosocial functioning of their geriatric patients might help physicians better balance medical interventions according to patients' needs. For this reason, we aimed to develop an easy-to-handle International Classification of Functioning, Disability and Health (ICF) Core Set for community-dwelling geriatric patients aged 75 and older in primary care. In this empirical study, we describe the functioning and health of community-dwelling patients aged 75 and older in primary care in Germany and identify the most common problems encountered by these individuals when using the ICF. Design: In this exploratory, cross-sectional study, a health professional conducted semi-structured interviews. Setting: Community-dwelling older adults aged 75 and older in Germany. Participants: 65 participants (mean age=80.2, SD=3.6). Outcome measures: Extended ICF Checklist V.2.1a, patients prioritised chapters of the 'activities and participation' component. Results: The three most common impairments for 'body functions' were visual system functions (ICF-code b210 ; 89%), blood pressure functions ( b420 ; 80%) and sensations associated with hearing and vestibular functions ( b240; 59% ). For 'body structures', they were eyes, ears and related structures ( s2 ; 81%), structure of mouth ( s320 ; 74%) and structures related to the digestive, metabolic and endocrine systems ( s5 ; 49%). For the 'activities and participation' component, adequate aids compensated for activity limitations to a certain degree. Still, after having adequate aids, the category in which the participants had the most difficulty was walking ( d450; 35%). Participants rated the 'mobility' chapter as the most important of all chapters. 'Environmental factors' were facilitators of participants' functioning. Conclusions: This empirical study provides a list of ICF categories relevant to older adults from the clinical perspective. Along with lists from the other three preparatory studies, it will form the basis for the development of an ICF Core Set for community-dwelling older adults in primary care. Trial registration details: The trial is registered in ClinicalTrials.gov (NCT03384732 ).